The use of home care as relational work: outlines for a research programme - Tove Harnett; Glenn Möllergren; Håkan Jönson (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Care has been theorized as a relational practice, but the research has focused on providers rather than users. Older care users have been cast in a passive role, and their relational activities to help with the provision of their care or to support those who provide it are underexplored. The purpose of this study is to develop knowledge about home care use as a form of relational ‘work’. Methods The data for the study consists of 34 qualitative interviews with home care users in Sweden and 15 observations of care provision. The data has been coded using thematic analysis. Results The analysis identifies two overlapping forms of relational work done by care users in the home care context: care-centred work, where care users work to facilitate care situations that were positive for staff and for the provision of care; and person-centred work, where care users work to foster personal relations by focusing on care staff as unique individuals. Conclusions The article proposes a research programme on relational work by care users, prompted by the finding that such efforts seem central for the understanding of eldercare in a variety of contexts.